Study On The Awareness Of Bumiputra Towards The Partial Concept Of Financial Planning In Terms Of Investment In Unit Trust Funds Provided By PNB - Borhan, Halimahton (2004)
This research project seeks to identify the awareness of Bumiputra towards the partial concept of financial planning in terms of investment in unit trust funds provided by PNB.The project initially introduces the reader to the Unit Trust in Malaysia especially Permodalan Nasional Berhad. The investigations goes to the result of primary research carried out through questionnaire surveys of the investors around ASNB counter located in the PNB Tower, Jalan Tun Razak.